Perbandingan Kadar Metabolit Sekunder Ekstrak Daun Sirih Cina (Peperomia Pellucida L. Kunth) Berdasarkan Faktor Intesitas Cahaya untuk Mendukung Perkuliahan Kimia Bahan Alam - Maharani, Aprilia; Hakim, Aliefman; Rahmawati, Rahmawati (Chemistry Education Practice, 2025)
This study aims to determine differences in levels of secondary metabolites of Chinese betel leaf extract which are affected by differences in light intensity and to determine the development of media posters as a means of supporting lectures on natural product chemistry. This research uses qualitative and quantitative methods of experiment and development. Based on the research results, Chinese betel leaf extract in sample 1 produced three secondary metabolites as well as sample 2. However, only two compounds could be compared between the two samples and these compounds were 3a(1H)-Azulenol, 2,3,4, 5,8,8a-hexahydro-6 and Dillapiole, while the compounds that cannot be compared are Cholest-5-en-3-ol(3 beta)-(CAS)lanol and Phenol,2,4-bis(1,1 -dimethylethyl)-(CAS) 2,4-Di-tert-butylphenol. The resulting level of the compound 3a(1H)-Azulenol,2,3,4,5,8,8a-hexahydro-6 (terpenoid) in sample 1 was 11.49% while in sample 2 it was 24.36%, and for the compound dillapiole (phenylpropanoid) content produced in sample 1 was 14.26% while in sample 2 it was 36.47%. For the compound cholest-5-en-3-ol (steroid) it produced a concentration of 74.25% in sample 1 while in sample 2 it was compound not detected and for the compound Phenol,2,4-bis(1,1-dimethylethyl)-(CAS ) 2,4-Di-tert-butylphenol (flavonoid) in sample 2 produced a level of 5.78% while in sample 1 it was compound not detected. Based on this, there were differences in the levels of secondary metabolites which were affected by light intensity. In developing poster media, stating that poster media is very feasible and practical to display so that poster media is not revised, this is based on the results of validity tests and trials.